Prediction of difficulties during laparoscopic cholecystectomy by preoperative clinical examination and ultrasonography - Kumar, Arun; Singh, Kunwar Vishal; Shakya, Jugendra Pal Singh; Sahu, Sangita; Dhiman, Soniya; Agrawal, Neelabh (International Surgery Journal, 2017)
Background: Cholelithiasis (gall stone disease) is a well-known disease worldwide. Ultrasonography is the most common screening test for cholecystitis and cholelithiasis. Laparoscopic Cholecystectomy is considered the treatment of choice for symptomatic gall stone disease. It is important to know the different clinical, radiological parameter and specific predictor that give some prediction of difficult LC. The aim of this study was to predict the difficulty of LC and the possibility of conversion to OC before surgery using the clinical and ultrasonographic criteria in our set up. Methods: The present study was carried out in the Department of surgery, Sarojini Naidu Medical College Agra, from November 2014 to October 2016. A total of 210 patients were enrolled for the laparoscopic cholecystectomy. All patients who were included in the study were undergone detailed history and clinical examination. A number of clinical and ultrasonographical parameters were noted. Results: Amongst the 210 patients admitted for laparoscopic cholecystectomy, 21 (10%) were male and 189 (90%) female, with age ranging from 12–60 years. The conversion rate in our study was 4.5% (9 of 210). In our study significant pre-operative factors which increased the conversion rate to open cholecystectomy includes male gender, obesity, abdominal scar of previous surgery, contracted and thickened gall bladder and patients having stone impacted at the neck of gall bladder. Conclusions: From this study, we conclude that preoperative ultrasonography is a good predictor of difficult laparoscopic cholecystectomy in the majority of cases and should be used as a screening procedure.